"Two‐Step" Raman Imaging Technique To Guide Chemo‐Photothermal Cancer Therapy. Issue 48 (13th August 2015) - Deng, Lin; Li, Qiujin; Yang, Yang; Omar, Haneen; Tang, Naijun; Zhang, Jianfei; Nie, Zhihong; Khashab, Niveen M.
Abstract: Graphene oxide‐wrapped gold nanorods (GO@AuNRs) offer efficient drug delivery as well as NIR laser photothermal therapy (PTT) in vitro and in vivo. However, no real‐time observation of drug release has been reported to better understand the synergy of chemotherapy and PTT. Herein, surface‐enhance Raman spectroscopy (SERS) is employed to guide chemo‐photothermal cancer therapy by a two‐step mechanism. In the presence of GO as an internal standard, SERS signals of DOX (doxorubicin) loaded onto GO@AuNRs are found to be pH‐responsive. Both DOX and GO show strong SERS signals before the DOX@GO@AuNRs are endocytic. However, when the DOX@GO@AuNRs enter acidic microenvironments such as endosomes and/or lysosomes, the DOX signals start decreasing while the GO signals remain the same. This plasmonic antenna could be used to identify the appropriate time to apply the PTT laser during chemo‐photothermal therapy. Abstract : One step at a time : Surface‐enhanced Raman spectroscopy (SERS) is employed to guide chemo‐photothermal cancer therapy through a two‐step mechanism. This method affords real‐time observation of drug release in vitro and in vivo to better understand the synergy between chemotherapy and photothermal therapy.